2020
DOI: 10.1002/ange.202005366
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Ring Opening Metathesis Block‐Like Copolymers and their Compositional Analysis by a Novel Retardation Technique

Abstract: Using a one‐step synthetic route for block copolymers avoids the repeated addition of monomers to the polymerization mixture, which can easily lead to contamination and, therefore, to the unwanted termination of chain growth. For this purpose, monomers (M1–M5) with different steric hindrances and different propagation rates are explored. Copolymerization of M1 (propagating rapidly) with M2 (propagating slowly), M1 with M3 (propagating extremely slowly) and M4 (propagating rapidly) with M5 (propagating slowly) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…This was totally contradictory to the block-like copolymer synthesized in one step using a mixture of fast and slow monomers reported by us previously. 36 From this observation we conclude that our initial hypothesis was correct and that the cross-propagations of monomers 11a and 10f must be virtually identical. In other words, both 10f and 11a are initiated equally quickly and hence statistically and, therefore, the retarded propagation of 10f can slow down the entire copolymerization.…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…This was totally contradictory to the block-like copolymer synthesized in one step using a mixture of fast and slow monomers reported by us previously. 36 From this observation we conclude that our initial hypothesis was correct and that the cross-propagations of monomers 11a and 10f must be virtually identical. In other words, both 10f and 11a are initiated equally quickly and hence statistically and, therefore, the retarded propagation of 10f can slow down the entire copolymerization.…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…When THF was used as the solvent for copolymerization on a mixture of a-NCA and b-NTA, using Boc-a-L-Lys NCA and Bn-b 3 -LCHG NTA as the model, we found no significant gradient separation in compositional profile of two amino acid subunits within the poly-a/b-peptide chain, though Boc-a-L-Lys NCA have a slightly higher reactivity than Bn-b 3 -LCHG NTA according to the kinetic plot of residual monomer (Figures 3A-3C) and instantaneous copolymer composition F a-NCA (Figures 3C and S19). (Gleede et al, 2019) This copolymerization proceeded close to ''ideal copolymerization'' (r a-NCA 3 r b-NTA = 0.93, r a-NCA 3 r b-NTA = 1 means ideal copolymerization) (Yasir et al, 2020), which in combination with the instantaneous copolymer composition F a-NCA revealed that the resulting poly-a/b-peptide was a random-like copolymer and the b-amino acid residue has a nearly even distribution along poly-a/b-peptide chain (Figure 3C) (Yasir et al, 2020). Poly-a/b-peptides have proven to be important mimics and modifications of nature polypeptides, such as host defense peptide (HDP), to effectively improve the stability upon enzymatic degradation and therapeutic potential (Konai et al, 2018;Schmitt et al, 2004Schmitt et al, , 2007.…”
Section: Accessmentioning
confidence: 77%
“…However, the synthesis of sequence-controlled polypeptides via polymerization is a long-lasting challenge (Jones, 2008;Lutz, 2010;Lutz et al, 2013). Therefore, a breakthrough in sequence-controlled poly-a/b-peptide synthesis is highly desired, though sequence-controlled polymerizations are reported recently on the synthesis of polyacrylates, polynorbornene, poly(styrene-b-maleimide) and polyesters (Jia et al, 2021;McGraw et al, 2020;Pfeifer and Lutz, 2007;Yasir et al, 2020). ll OPEN…”
Section: Introductionmentioning
confidence: 99%